2008
DOI: 10.1210/en.2008-0747
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Nesfatin-1 Immunoreactivity in Endocrine Cell Types of the Rat Gastric Oxyntic Mucosa

Abstract: Hypothalamic nesfatin-1, derived from the nucleobindin2 (NUCB2) precursor, inhibits nocturnal food intake and body weight gain in rats. Nesfatin-1 is able to cross the blood-brain barrier, suggesting a peripheral source of nesfatin-1. Many centrally acting food intake regulatory neuropeptides are also produced in the periphery, especially in the gastrointestinal tract. Therefore, we investigated the gene expression of NUCB2 and distribution of nesfatin-1-immunoreactive cells in the stomach. Microarray mRNA exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
319
0
16

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 302 publications
(353 citation statements)
references
References 30 publications
18
319
0
16
Order By: Relevance
“…In the present study, only the full length NUBC2 was detected by Western blot. The antibody used was raised against mature nesfatin-1 amino acids 1-82 and shown before to detect synthetic nesfatin-1 peptide as well as full length NUCB2 which also contains the epitope [36]. So far, only one study described the occurrence of mature nesfatin-1 peptide in the cerebrospinal fluid of rats, whereas in brain nuclei only full length NUCB2 was detected [24].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, only the full length NUBC2 was detected by Western blot. The antibody used was raised against mature nesfatin-1 amino acids 1-82 and shown before to detect synthetic nesfatin-1 peptide as well as full length NUCB2 which also contains the epitope [36]. So far, only one study described the occurrence of mature nesfatin-1 peptide in the cerebrospinal fluid of rats, whereas in brain nuclei only full length NUCB2 was detected [24].…”
Section: Discussionmentioning
confidence: 99%
“…So far, only one study described the occurrence of mature nesfatin-1 peptide in the cerebrospinal fluid of rats, whereas in brain nuclei only full length NUCB2 was detected [24]. In all subsequent reports, only full length NUCB2 was detected by Western blot [8,27,36] or studies performing immunostaining did not distinguish between NUCB2 protein and nesfatin-1 peptide [5,6,8,10,13,14,16,18,25,32,34,42,43]. Since also full length NUCB2 exerts an anorexigenic effect it is also possible that this protein is the active circulating form.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nesfatin-1 was detected mainly within the central nervous system, in the arcuate nucleus, supraoptic nucleus, hypothalamus, and spinal cord (13). It was contained in the central part of the pancreatic islets, liver, spleen, thymus, heart, liver, muscle, pituitary glands, testes, fat tissue, and endocrine cells of the digestive tract (13,29,33). As an anorectic hormone, nesfatin-1 takes part in appetite regulatory processes, in regulation of body weight, fat mass, glucose levels, insulin secretion, and energy homeostasis (14,29).…”
mentioning
confidence: 99%
“…It was contained in the central part of the pancreatic islets, liver, spleen, thymus, heart, liver, muscle, pituitary glands, testes, fat tissue, and endocrine cells of the digestive tract (13,29,33). As an anorectic hormone, nesfatin-1 takes part in appetite regulatory processes, in regulation of body weight, fat mass, glucose levels, insulin secretion, and energy homeostasis (14,29). Although it has been found that nesfatin-1 influences gastrointestinal motility and reduces gastric acid secretion (2,30,31), the functional roles of this peptide in the digestive tract are not completely understood.…”
mentioning
confidence: 99%